2015
DOI: 10.1111/jth.12915
|View full text |Cite
|
Sign up to set email alerts
|

αIIbβ3: structure and function

Abstract: Summary During the past decade, advanced techniques in structural biology have provided atomic level information on the platelet integrin αIIbβ3 activation mechanism that results in it adopting a high-affinity ligand-binding conformation(s). This review focuses on advances in imaging intact αIIbβ3 in a lipid bilayer in the absence of detergent and new structural insights into the changes in the ligand-binding pocket with receptor activation and ligand binding. It concludes with descriptions of novel therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 68 publications
0
45
0
Order By: Relevance
“…α IIb β 3 is essential for platelet-mediated hemostasis and thrombosis 31, 32 , while α V β 3 is important in tumor angiogenesis, metastasis, and inflammation 33, 34 . It has been reported that the α V β 3 glycosylation differs significantly between primary and metastatic melanoma cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…α IIb β 3 is essential for platelet-mediated hemostasis and thrombosis 31, 32 , while α V β 3 is important in tumor angiogenesis, metastasis, and inflammation 33, 34 . It has been reported that the α V β 3 glycosylation differs significantly between primary and metastatic melanoma cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Only stimulation by agonists at the sites of wounds turns on the fibrinogen binding function of α IIb β 3 integrins, which then leads to aggregation of platelets and the formation of a thrombus, halting the loss of blood. The transition between the ‘on’ and ‘off’ affinity states is referred to as activation (for reviews see Banno and Ginsberg 2008; Luo et al 2007; Bouaouina et al 2012; Ye et al 2012; Coller 2015). Many of the current models of integrin’s molecular activation mechanism have been primarily inferred from crystal structures of β 3 integrin extracellular domains (Xiong et al 2001, 2002, 2009; Zhu et al 2008, 2009, 2013; Dong et al 2012) as well as two-dimensional negativestain electron microscopy (Luo et al 2007; Nishida et al 2006; Takagi et al 2002; Xie et al 2010; Ye et al 2010; Zhu et al 2008; Dai et al 2015; Su et al 2016; Eng et al 2011).…”
Section: 1 Introductionmentioning
confidence: 99%
“…Three agents targeting α IIb β 3 have been approved for human use in the USA, starting with abciximab, a monoclonal antibody fragment, followed by eptifibatide, a cyclic peptide, and tirofiban, a peptidomimetic molecule [28]. These drugs have shown efficacy in the adjunctive therapy to ischemic complications of percutaneous coronary interventions in a large number of randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…RUC-1 (a small molecular inhibitor of integrin α IIb β 3) only binds to the α IIb subunit but not to β 3 and does not induce conformational changes of α IIb β 3. By avoiding such a change, it is anticipated that associated thrombocytopenia, induction of fibrinogen binding, and paradoxical platelet activation would be prevented [28, 30]. RUC-2 and RUC-4 were developed following RUC-1.…”
Section: Discussionmentioning
confidence: 99%